Bacterial culturing is crucial to boost sustainable agriculture. Issue 1 (January 2023) - Mapelli, Francesca; Mengoni, Alessio; Riva, Valentina; Borin, Sara
Abstract: The huge amount of information on microbiomes gained through the advancement of high-throughput sequencing methods has been translated only partially into concrete solutions for societal needs. Here, we highlight that bacterial culturing remains pivotal in microbiology and is crucial for the effective application of plant probiotics in sustainable agriculture.